“Reformationstag” 500. International symposium in Bucharest: “The Protestant Reformation. History, Reception, and Influences” - Fănel ȘUTEU (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2018)
„The Protestant Reformation. History, Reception and Influences”: an emblematic meeting under the form of an international scientific symposium of the Pentecostal Theological Institute from Bucharest, Romania (I.T.P.B.). The event took place on the the18th and 19th of May 2017 and was organized by Assoc. Prof. EMANUEL CONŢAC (I.T.P. Bucharest) and by Senior Lect. ROMULUS GANEA (I.T.P. Bucharest). The Romanian inaugural timer anticipated the German augural gong of the 31st of October 1517, on the eve of “All Saints’ Day” [Allerheiligen], which became later on, for a part of Christendom, “The Reformation Day” [Reformationstag]. The event that took place half a millennium ago was thus recalled: an event through which the symbolic gesture of the monk and theologian Martin Luther, who posted the ninety-five theses “against the traffic in indulgences” (M. Malherbe) on the door of the Castle Church in Wittenberg, expressed an already existing fracture in the midst of the Catholic Church, the appearance of the Reformation and the birth of Protestantism.